The Level of Knowledge and Support of Husband With Exclusive Breastfeeding at Padang - dewi susilawati (Universitas Andalas, 2019)
World breastfeeding coverage according to Indonesia is 55.7%, this coverage is still below the target of 80%. Factors The causes of low exclusive breastfeeding in Indonesia include factors of knowledge and support of the husband.This study was analytical with a design cross-sectional carried out in the Aia Pacah Sub-districts Air Dingin Health Center on June 21 -1 July 2018. Samples in this study were all husbands who had 6-12 months infants, a total sampling technique of 46 people. The data used were primary data which the instrument filled out the questionnaire directly by the respondents, the data was processed by editing, coding, entry, cleaning, and processing and analyzed using univariate and bivariate analysis with statistical test chi-square. The results of the study found that statistical tests using Chi-Square with a significance level of 95%, the p-value <0.005 is 0.004, p value> 0.05, which is 0.705. The conclusion of this research is that there is a relationship between the level of knowledge with exclusive breastfeeding and there is no relationship between husband's support and exclusive breastfeeding.